Parental suicide attempt and subsequent risk of pre‐enlistment suicide attempt among male and female new soldiers in the U.S. Army. Issue 1 (1st June 2021) - Wang, Jing; Naifeh, James A.; Mash, Holly B. Herberman; Morganstein, Joshua C.; Fullerton, Carol S.; Cozza, Stephen J.; Stein, Murray B.; Ursano, Robert J.
Abstract: Objective: Suicide and suicide attempts among U.S. Army soldiers are a significant concern for public health. This study examined the association of parental suicide attempt prior to age 13 of the soldier with subsequent risk of pre‐enlistment suicide attempt. Method: We conducted secondary analyses of survey data from new soldiers who participated in the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS) ( N  = 38, 396). A series of logistic regression analyses were conducted. Results: Of all new soldiers, 1.4% reported that they attempted suicide between age 13 and entering the Army, and 2.3% reported a parental suicide attempt prior to age 13. Parental suicide attempt was associated with increased odds of subsequent suicide attempt; however, this association was moderated by gender and was significant only among male soldiers. The association between parental suicide attempt and pre‐enlistment suicide attempt among male soldiers was still significant after controlling for socio‐demographic characteristics, soldier/parental psychopathology, and childhood adversities. Conclusions: These results highlight parental suicide attempt as a unique pre‐enlistment risk factor for suicide attempt, especially among male new soldiers. Further studies are needed to separate the genetic and environmental contributions to intra‐familial risk for suicidal behavior.